2013
DOI: 10.14419/ijbas.v2i2.896
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Remote Sensing for Identification of Solar Potential Sites in Pakistan

Abstract: Renewable energy sources and technologies have the potential to provide solutions to the long-standing energy problems being faced by the developing countries like Pakistan. Pakistan is endowed with various renewable energy resources such as solar, hydal, wind, biofuel and geothermal. It can earn dividends if these resources are explored, exploited and developed. Pakistan lies in an area of one of the highest solar insulation in the world. The aim of this paper was to identify the areas receiving maximum solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In these areas the sun shines in the range of 2300-2700 h per year [18]. In [19] the authors have evaluated the most suitable sites for solar PV systems, keeping in view the monsoon weather. The authors of [19] concluded that District Multan and Dera Ghazi Khan are best for installing the solar PV power plants.…”
Section: Solar Sites In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…In these areas the sun shines in the range of 2300-2700 h per year [18]. In [19] the authors have evaluated the most suitable sites for solar PV systems, keeping in view the monsoon weather. The authors of [19] concluded that District Multan and Dera Ghazi Khan are best for installing the solar PV power plants.…”
Section: Solar Sites In Pakistanmentioning
confidence: 99%
“…In [19] the authors have evaluated the most suitable sites for solar PV systems, keeping in view the monsoon weather. The authors of [19] concluded that District Multan and Dera Ghazi Khan are best for installing the solar PV power plants. These districts are located in southern Punjab along the provincial boundary of Balochistan and Punjab.…”
Section: Solar Sites In Pakistanmentioning
confidence: 99%
“…The algal blooms in stagnant waters and rivers are due to the suitable temperature and solar illumination prevailing throughout the year in most parts of the country. Geographically Pakistan lies in the world's greatest solar insulation area, receiving high intensity of solar radiations due to favorable climatic conditions [83,84]. To identify solar potential of the country the solar climate of Pakistan has been elaborately studied by Raja [85].…”
Section: Prospects Of Cost Effective Microalgal Cultivationmentioning
confidence: 99%
“…Potential of solar energy in Pakistan has been estimated at over 100,000 MW [86]. An average of 5.5 KW/m 2 of the solar radiations is received by the country during 300 or more clear days per annum [81,84]. Solar map (Fig.…”
Section: Prospects Of Cost Effective Microalgal Cultivationmentioning
confidence: 99%
“…Most area of country, mainly Baluchistan, Sindh, and southern Punjab get plentiful solar irradiation approximately 2 MW hr/m2 and 3000 hrs of sunlight per year, which is the great average amount of solar radiation in the world (Ahmed, Zafran, Khan, Waqar & Hasan, 2017;Tahir & Asim, 2018). Pakistan has predictable solar energy more than 100,000 MW (Basir, Aziz, Ahmad & Wahid, 2013). Sunlight carries radiant energy to the surface of the earth.…”
Section: Introductionmentioning
confidence: 99%